SMART VILLAGE MELALUI SISTEM GIGADES DI DESA KOTO BENAI KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI TAHUN 2022-2023 - ,, Aprinaldi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Gigades is a digital service system in the form of an application and website designed as a medium to facilitate village governments in managing administration and also facilitate the public in obtaining administrative services via smartphones. Koto Benai Village is one of the villages that implements the gigades system. Researchers are interested in knowing how the gigades system is implemented in Koto Benai Village. This study aims to describe in depth public services in reporting village administration management which has currently been implemented with the implementation of the gigades system in Koto Benai Village, Benai District, Kuantan Singingi Regency. This study uses a descriptive qualitative research type. The theory used is smart village in Herdiana (2019) which has three dimensions in smart village development: smart government, smart community, smart environment. The results of this study indicate that the implementation of the gigades system is still not optimal. This is evident from the still low use of the gigades system. There are several factors that cause the implementation of the gigades system to be less than optimal, namely (1) the lack of socialization and training conducted by the Koto Benai Village government to the community so that many people still do not understand how to use gigades. (2) lack of human resources to manage the Gigades system in Koto Benai Village. (3) many people do not have smartphones that support the use of the Gigades application. Keyword: E-Government, Smart Village, Public Service.